Relação entre circunferência da panturrilha e indicadores da função cardiovascular de pacientes com doença arterial periférica - Ferreira, Fabiana Gonçalves (2021)
Patients with peripheral arterial disease (PAD) have decreased calf muscle area, damage to muscle fibers, impaired mitochondrial function and apoptosis due to the chronic ischemia process, causing losses in physical activity and cardiovascular health. However, there is no evidence on the potential role of calf circumference (CC) measurement and its relationship with cardiovascular health indicators in these patients. The aim of the present study was to evaluate the relationship between CC and cardiovascular function indicators in patients with PAD. Patients with PAD in São Paulo were recruited from 2015 to 2019. Anthropometric data including CC and cardiovascular indicators were obtained: blood pressure, arterial stiffness indicators and heart rate variability (HRV) indicators. For data analysis, binary logistics were used, with the first quartile of CC as risk. The multivariate analysis used age and ankle brachial index (ABI) as adjustments. CC was associated with ABI in both sexes (men: OR=4.998, p=0.005; women: OR=2.289, p=0.029). In women, there was an association between CC and the increase index corrected by 75 bpm (OR=4.438, p=0.015). In men, there was an association between CC and rMSSD (OR=3.010, p=0.011), pNN50 (OR=2.695, p=0.018), low frequency bands (OR=6.315, p<0.001) and high frequency bands (OR=6.314, p<0.001). In conclusion, in patients with PAD, CC was associated with cardiovascular indicators and ABI. In women, this association was established with indicators of arterial stiffness, in men with indicators of HRV.